Endoscopic Experience Improves Interobserver Agreement in the Grading of Esophagitis by Los Angeles Classification: Conventional Endoscopy and Optimal Band Image System - Lee, Si Hyung; Jang, Byung Ik; Kim, Kyeong Ok; Jeon, Seong Woo; Kwon, Joong Goo; Kim, Eun Young; Jung‡, Jin Tae; Park, Kyung Sik; Cho, Kwnag Bum; Kim, Eun Soo; Park, Chang Geun; Yang, Chang Heon (Gut and liver, 2014)
Interobserver variation by experience was documented for the diagnosis of esophagitis using the Los Angeles classification. The aim of this study was to evaluate whether interobserver agreement can be improved by higher levels of endoscopic experience in the diagnosis of erosive esophagitis. Endoscopic images of 51 patients with gastroesophageal reflux disease (GERD) symptoms were obtained with conventional endoscopy and optimal band imaging (OBI). Endoscopists were divided into an expert group (16 gastroenterologic endoscopic specialists guaranteed by the Korean Society of Gastrointestinal Endoscopy) and a trainee group (individuals with fellowships, first year of specialty training in gastroenterology). All endoscopists had no or minimal experience with OBI. GERD was diagnosed using the Los Angeles classification with or without OBI. The mean weighted paired κ statistics for interobserver agreement in grading erosive esophagitis by conventional endoscopy in the expert group was better than that in the trainee group (0.51 vs 0.42, p<0.05). The mean weighted paired k statistics in the expert group and in the trainee group based on conventional endoscopy with OBI did not differ (0.42, 0.42). Interobserver agreement in the expert group using conventional endoscopy was better than that in the trainee group. Endoscopic experience can improve the interobserver agreement in the grading of esophagitis using the Los Angeles classification.